A study exploring factors of decision to text while walking among college students based on Theory of Planned Behavior (TPB). Issue 8 (16th November 2016) - Koh, Hyeseung; Mackert, Michael
ABSTRACT: Objective : This study attempted to identify critical predictors of intention to both send and read texts while walking based on Theory of Planned Behavior in order to provide resources for practitioners and campaign designers to inform college students of the perils of texting while walking and dissuade them from such a risky behavior.Participants : Three hundred twenty-nine college students were recruited from a large public university in the Southwest in September 2014.Methods : This study used a cross-sectional survey design.Results : Subjective norm (sending: B = .17, p = .02; reading: B = .17, p = .04), personal norms (sending: B = −.32, p = .001, reading: B = −.35, p = .001), and self-efficacy (sending: B = −.27, p = .001; reading: B = −.24, p = .001) were significant predictors of intention to both send and read text messages while walking.Conclusions : For students who have greater intention of texting while walking, persuasive communication should utilize normative influence and self-efficacy to discourage texting while walking.